Pemodelan Efisiensi Bank di Indonesia: Perbandingan antara Bank Syariah dan Bank Konvensional - Ar Royyan Ramly; Abdul Hakim (Esensi: Jurnal Bisnis dan Manajemen, 2017)
Modeling of Indonesian Banks' Efficiency: Comparative Study Between Islamic Banks and Conventional BanksThis study aims to analyze the efficiency comparison between Islamic banks and conventional banks in Indonesia in 2012-2014. The method used in this study is non-parametric approach with data envelopment analysis (DEA) and Panel data regression whereas input and output variables are treated in intermediary function. To measure the efficiency level of Islamic banks and conventional banks the independent sample t test is used. The result of the study shows that there is significant difference of efficiency between Islamic banking and conventional banking in 2012-2014. The empirical factors that affect Islamic banks and Conventional banks efficiency are ROA, CAR, and FDR variables. On the other hand, NPF results insignificantly and affects negatively towards Islamic banks efficiency. Lastly, ROA, NPL, LDR, and CAR had significantly affected Conventional banks efficiency.DOI: 10.15408/ess.v7i2.4989